Upaya Pemulihan Pariwisata Korea Selatan dari Pandemi COVID-19 - Gita Bunga Bahari (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The COVID-19 pandemic that has hit the world gave impacts in all aspects of life, one of them is tourism. The enforced of social restrictions and banned on entry for foreign tourists has forced countries to face a crisis in the tourism sector, and South Korea is not an exception. South Korea, which has become a popular destination among foreign tourists along with the global Korean Wave, has to face a downturn in the tourism sector due to the COVID-19 pandemic since the number of foreign tourists has decreased drastically. This research aims to examine the efforts made by the South Korea’s government during the COVID-19 pandemic by using the concept of digital diplomacy which is an extension of the theory of public diplomacy. The result shows that the South Korean’s government actively carried out tourism promotion through social media during the COVID-19 pandemic and able to attract the international public’s attention through creative means. Through tourism promotion on social media, the South Korea’s government wants to build an image as a country with creative destinations and influence foreign tourists to make South Korea their main destination when the pandemic ends. The efforts of the South Korean government have shown positive results, but still require improvement so that South Korean tourism can quickly recover to what it was before the COVID-19 pandemic occurred.